2019
DOI: 10.1109/access.2019.2893629
|View full text |Cite
|
Sign up to set email alerts
|

A SINR-Based Synchronization Protocol for D2D Communications in Public Safety

Abstract: Device-to-device (D2D) communication, an emerging form of wireless communication, has attracted considerable attention, but an efficient synchronization protocol has not yet been developed. This has crucial implications for public safety applications that lack sufficient network infrastructure. In the public safety applications, the cellular network may not be available or fully functional when the base stations are malfunctioned or destroyed due to disasters, such as an earthquake, a tsunami, or an attack. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Based on D2D communication paradigm, a disaster resilient multi-hop D2D communication network is proposed in [38], which offers shortest path routing based scheduling in terms of user coverage in the affected disaster area. Whereas an effective mobile synchronization protocol is developed for establishing a synchronized mobile network to provide enhanced coverage in public safety communication [39]. This synchronization protocol works on the assessment of signal-to-interference-plus-noise ratio to assist D2D users in forward timing signal.…”
Section: Brckmentioning
confidence: 99%
“…Based on D2D communication paradigm, a disaster resilient multi-hop D2D communication network is proposed in [38], which offers shortest path routing based scheduling in terms of user coverage in the affected disaster area. Whereas an effective mobile synchronization protocol is developed for establishing a synchronized mobile network to provide enhanced coverage in public safety communication [39]. This synchronization protocol works on the assessment of signal-to-interference-plus-noise ratio to assist D2D users in forward timing signal.…”
Section: Brckmentioning
confidence: 99%
“…The author in [154] proposed caching strategy for D2D-assisted wireless emergency communication in order to maximize the effective capacity subject to delay constraint and conducted a numerical simulation to elaborate the performances of their proposed strategies. The authors in [157] developed SINR based synchronization protocol to help users in a victim area to establish a synchronized communication for public safety applications. Through numerical simulation, the authors have shown that their proposed protocol enabled more than 90% of the D2D device can successfully synchronize with the network, whereas only 75% of D2D users can successfully be connected with the network through the conventional protocols.…”
Section: D2d Resource Optimization For Efficient Emergency Servicementioning
confidence: 99%
“…[156] NP optimization problem Proposed multi antenna precoding strategy and multi hop D2D communication to provide reliable communication and extended UAV coverage for disaster relief. [157] Stochastic optimization problem developed an SINR based synchronization protocol for D2D based Public Safety communications. [158] Stochastic optimization problem exploited energy harvesting relaying strategy with simultaneous information and power transfer to extend lifetime of energy constrained D2D based Public Safety network.…”
Section: Table 8 Resource Optimization For D2d-based Public Safety Co...mentioning
confidence: 99%